Thermoneutrality results in prominent diet‐induced body weight differences in C57BL/6J mice, not paralleled by diet‐induced metabolic differences. Issue 4 (18th November 2013) - Hoevenaars, Femke P. M.; Bekkenkamp‐Grovenstein, Melissa; Janssen, Rolf J. R. J.; Heil, Sandra G.; Bunschoten, Annelies; Hoek‐van den Hil, Elise F.; Snaas‐Alders, Sophie; Teerds, Katja; van, Evert M.; Keijer, Jaap
<x xml:space="preserve">Abstract</x> Scope Mice are usually housed at 20–24°C. At thermoneutrality (28°C) larger diet‐induced differences in obesity are seen. We tested whether this leads to large differences in metabolic health parameters. Methods and results We performed a 14‐wk dietary intervention in C57BL/6J mice at 28°C and assessed adiposity and metabolic health parameters for a semipurified low fat (10 energy%) diet and a moderate high fat (30 energy%) diet. A large and significant diet‐induced differential increase in body weight, adipose tissue mass, adipocyte size, serum leptin level, and, to some extent, cholesterol level was observed. No adipose tissue inflammation was seen. No differential effect of the diets on serum glucose, free fatty acids, triacylglycerides, insulin, adiponectin, resistin, PAI‐1, MMP‐9, sVCAM‐1, sICAM‐1, sE‐selectin, IL‐6, ApoE, fibrinogen levels, or HOMA index was observed. Also in muscle no differential effect on mitochondrial density, mitochondrial respiratory control ratio, or mRNA expression of metabolic genes was found. Finally, in liver no differential effect on weight, triacylglycerides level, aconitase/citrate synthase activity ratio was seen. Conclusion Low fat diet and moderate high fat diet induce prominent body weight differences at thermoneutrality, which is not paralleled by metabolic differences. Our data rather suggest that thermoneutrality alters metabolic homeostasis.